FEATURES OF THE α-AZAHETARYL-2-HYDROXYACETOPHENONES REACTION WITH CHLOROACETYL CHLORIDE (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
The reaction of α-azolyl-2-hydroxyacetophenones with chloroacetyl chloride in acetonitrile in the presence of pyridine resulted in 2-chloromethyl-3-azolylchromones, while both the α-(2-pyridyl) and α-(2-quinolyl) derivatives formed the products of the subsequentintramolecular cyclization with annelation of indolizine or pyrroloquinoline ring to the chromone core.
Keywords: acylation, intramolecular cyclization, α-azahetaryl-2-hydroxyacetophenones, 3-azolyl-2-chloromethyl-7-hydroxy-4Hchromen- 4-ones, 12H-chromeno[3,2-a]indolizin-12-ones, 7H-chromeno[3',2':3,4]pyrrolo[1,2-a]quinolin-7-ones.